Islamic Educational Values in 29 Juz Harga Wanita Novel By Ma'mun Affany - Yeny Saswita (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2018)
This study aims to describe and analyze the existing religious messages in a 29 Juz Harga Wanita novel, which is about the value of Islamic Education in Novel by Ma'mun Affany. The method used in this study is interpretive research, i.e. research that performs analysis to get the meaning of a phenomenon and aims to gain a deep understanding, especially the value of Islamic education and its relevance in novel 29 Juz Harga Wanita by Ma'mun Affany. This study focuses on literature review, which is utilizing the source library to obtain research data without doing field research. Make the novel as an educational medium by taking lessons from the messages contained therein. The data are grouped into three kinds, namely (1) the data of the faith value in the 29 Juz Harga Wanita novel which includes (a) faith in God; (b) faith in the books of God; (c) faith in qada and qadar, (2) data of religious devotion values in 29 Juz Harga Wanita novel that includes (a) Istiqomah (sticking to religion) (b) Ikhtiar (try and pray); (c) obey the prayer; (d) tawaadlu (humble/not arrogant); (e) qona'ah (willing and sufficient for all that is owned); and 3) data of noble values in 29 Juz Harga Wanita novel which includes: (a) nobility to Allah, (b) noble character to man that is to self, family, neighbor, society; and (c) nobility to the environment. As rahmatan lil Alamin, Islam placed women in a glorious place. Islam is a religion that respects and appreciates women and men to God in absolute terms. There is relevance between the values of Islamic Religious Education in 29 Juz Harga Wanita novel, with the goal of Islamic religious education that is to invite humans to do good and avoid bad nature in accordance with the norms that have been established by Islam. Islam has given a clear concept about the procedure or process of a marriage based on the Qur'an and the Sunnah as-saheeh. Keywords: Value of Islamic Education, 29 Juz Harga Wanita Novel, Ma'mun Affany